INFORMATION AND COMMUNICATION TECHNOLOGIES: THE PERSPECTIVE OF THE URGENCY AND EMERGENCY MOBILE CARE SERVICE PROFESSIONALS - Mendonça, Renata Rodrigues; Salvador, Drielly Lima Valle Folha; Mata, Trindade Cristina Furlan da; Nakasima, Pedro Augusto Masashiro; Derenzo, Neide; Covre, Eduardo Rocha; Costa, Maria Antonia Ramos (Cogitare Enfermagem, 2022)
Objective: to assess the interest, access and knowledge of the Urgency and Emergency Mobile Care Service professionals in relation to Information and Communication Technologies in such service. Method: a descriptive and cross-sectional study conducted with Urgency and Emergency Mobile Care Service professionals (physicians, nurses, nursing technicians and drivers) in September and October 2020 in the Northwest region of the state of Paraná, Brazil. The data were collected through a structured instrument and analyzed by means of descriptive statistics. Results: of the 30 participants, 80% reported access only to a simple cell phone, and 86.7% believed in the viability of a computerized system to assist in care provision and in the improvement of the response time for the event. Conclusion: despite the technological deficit in the service researched and dissatisfaction of its professionals, they wish for technologies to streamline care, thus reducing the response time for the event. Thus, the results can support management of the services and bring about positive contributions to the SAMU team professional practice.